Taḥlīl Tanmiyyah Mawād Ta’līm al-Lugah al-‘Arabiyyah fī Kitāb al-Dirāsī lil-Faṣl al-Tāsi’ al-Mustawā al-Ūla: Analyze Development of Arabic Teaching Material on Arabic Textbook in First Semester of 9th Grader - Labibah Zulfa, Hasna; Muhdi, Ali (Lisanul Arab: Journal of Arabic Learning and Teaching, 2024)
Textbooks are very important in the implementation of learning in the classroom. however, there are often errors in writing and incongruity of material in textbooks. therefore, it is necessary to analyze the content of textbooks, in this study, researchers chose to analyze textbooks in terms of the principles of developing Arabic teaching materials. This research used literature research method with the object of research on Arabic Language Textbook for Grade 9 First Semester by MGMP Arabic Language Purbalingga. Meanwhile, in analyzed the data, the researchers used content analysis techniques. This research aims to: 1) How is the analysis of Arabic Language Textbook Grade 9 First Semester based on the principles of teaching material development, 2) How is the development of Arabic Language Textbook for Grade 9 First Semester based on the principles of teaching material development.The results of this study are:1) From the results of the analysis of Arabic textbooks for Grade 9 First Semester of the academic year 2022/2023 based on the principles of developing teaching materials, there are, psychological principles, social and cultural principles, also educational and linguistic principles, it can be seen that this book has fulfilled psychological principles and social and culture principles. Meanwhile, there are some shortcomings were found in linguistic and educational principles. 2) From these shortcomings, this textbook needs to be developed based on the educationl and linguistic principles to make it better and more feasible to use.